(untitled) (International journal of artificial intelligence, 2024)
This paper explores the impact of artificial intelligence (AI) in language learning, focusing on its revolutionary role in enhancing language education. AI tools, such as virtual tutors, chatbots, and learning applications, provide tailored and adaptable learning experiences for individuals. The study highlights how AI improves grammar, vocabulary, pronunciation, and conversational abilities, while also addressing challenges such as privacy concerns and limited human interaction. Findings suggest that AI effectively complements traditional teaching methods, enhancing engagement and learning efficiency for various learners.